Studies on the effect of times of patch budding in Aonla (Indian Journal of Arid Horticulture, 2013)
The present experiment was carried out at Fruit Research Station, Kuthulia, College of Agriculture, Rewa (M.P.)  st st th st during 2008-09. The investigation was carried out on ten treatments i.e., 21 September, 01 October, 11 October, 21 st th st st th st October, 01 November, 11 November, 21 November, 01 April, 11 April and 21 April in a randomized block design  with four replications. The results showed that the maximum bud sprouting percentage (69.25 %), survival percentage  (64.50 %), bud take success percentage (58.75 %), leaf chlorophyll content (5.65), shoot length, shoot diameter and  st number of leaves per sprouted shoot were recorded in the month of 21 April. However, maximum time taken for bud  st sprouting (30.75 days) was found in 21 November. Whereas, minimum bud sprouting percentage (24.75 %), survival  percentage (22.50 %), bud take success percentage (14.25 %), shoot length, shoot diameter and number of leaves per  st sprouted shoot were recorded in the month of 21 November. However, minimum time taken for bud sprouting was found  st st st in 21 April and leaf chlorophyll content (3.04) in 1 November. The results reveal that date of budding 21 April was  significant superior to all other date of budding. However shoot length per sprout at 90 days after operation, shoot diameter  per sprout at 15, 45, 60 and 90 days after operation and number of leaves sprouted shoot at 60, 75 and 90 days after operation  th st were non- significant. The patch budding given best suitable period obtained from the month 11 April to 21 April.
Keywords: Aonla; patch budding; time of propagation